Are tennis players at increased risk for low back pain and sciatica? - Saraux, A.; Guillodo, Y.; Devauchelle, V.; Allain, J.; Guedes, C.; Le Goff, P. (Revue du Rhumatisme, 1999)
OBJECTIVE: Tennis practiced intensively is generally held to be a risk factor for low back pain. The objective of our study was to evaluate the prevalence of low back pain with or without sciatica during the last week in tennis players versus controls. PATIENTS AND METHODS: During an international tennis competition held in Brest, France, ten physicians or medical students interviewed 633 spectators older than 18 years and divided them into tennis players and controls. The sample size was selected to allow detection of a twofold increase in the risk of low back pain in tennis players (with alpha = 5% and 1-beta = 80%). RESULTS: Of the 633 subjects, 388 were and 245 were not tennis players. There were 421 men with a mean age of 37 +/- 13.7 years and 212 women with a mean age of 34.3 +/- 12.7. Among the men, 49 of the 281 tennis players (17.4%) reported low back pain during the last week versus 26 of the 140 controls (18.6%). Corresponding figures in women were 20 of 107 tennis players (18.7%) and 29 of 105 controls (27.6%). Sciatica was not more common in tennis players (men, 20 of 281 tennis players [7.1%] versus 6 of 140 controls [4.3%]; women, 8 of 107 tennis players [7.5%] versus 10 of 105 controls [9.5%]). None of the differences between tennis players and controls were significant. The number of hours spent playing tennis per week was similar in tennis players with and without low back pain. CONCLUSION: Our interview-based cross-sectional study found no evidence that playing tennis involves a higher risk of low back pain with or without sciatica.